Can you make a scary face? - Thomas, Jan, 1958- (New York : Beach Lane Books, 2009)
A ladybug invites the reader to play a game of "let's pretend.".
Kirkus Review
1.4
K-3.
K-3
Keywords: Frogs -- Juvenile fiction; Imagination -- Juvenile fiction; Ladybugs -- Juvenile fiction; Frogs -- Fiction; Imagination -- Fiction; Ladybugs -- Fiction; Frogs -- Fiction; Imagination -- Fiction; Ladybugs -- Fiction; Picture Books for children